Contemporary approaches to isokinetic strength assessments in professional football players. Issue 3 (2nd September 2017) - Eustace, Steven James; Page, Richard Michael; Greig, Matt
ABSTRACT: Purpose: To assess traditional and novel isokinetic strength characteristics of the eccentric knee flexor (eccKF) and concentric knee extensor (conKE) musculature, 26 professional football players completed bilateral conKE and eccKF contractions at angular velocities of 180, 270, and 60° · s −1 .Method: Peak torque (PT), angle of peak torque (APT), angle-specific torque (AST) analysed every 10° between 40° and 70°, functional range (FR), and dynamic control ratios (DCR) calculated from both the PT (DCRPT ) and AST data (DCRAST ) were analysed.Results:  The PT, APT, and FR data elicited significant contraction*angular velocity interactions ( P  < 0.001). Significant main effects for contraction*angular velocity*angle and contraction*angular velocity*limb*angle interactions ( P  ≤ 0.001) were identified for AST data. The DCRPT data elicited a significant main effect for angular velocity ( P  < 0.001) and limb ( P  = 0.018), whereas the DCRAST data were significantly different across angles ( P  < 0.001) and elicited a significant ( P  = 0.002) limb*angle interaction.Conclusion:  Traditional analysis variables utilised for isokinetic strength assessments in football may not be appropriate and/or sensitive enough to identify injury risk. Practitioners should utilise the novel metrics proposed in the current study and conduct assessments across a range of joint angles and angular velocities.